Roles of general physicians in proper utilizing stroke rapid response team Review - Dr.Albara munir dahlawi; Dr.Ali Hassan Almaqsudi; Dr.Ahmed Labib Almanzalawi; Dr.Eyaad talat ghallab; Dr. Majed Ahmed Almogbel; DR.Moayad Yahya Mohammed Zakari; Dr.Rawan ezzi Abufaia; Mohammad Saleh helwan AlGhamdi; Abdullah Ali Babaalghayth; Atallah Murshid Al-Budhaili; Dr. Bassam Mohammed Maghram Assiri; Dr.Abdulaziz Sharif Adam; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Stroke patients require prompt treatment due to the time-sensitive advantages of reperfusion treatments. The percentage of patients qualified for reperfusion therapy is restricted, as numerous patients do not promptly alert healthcare professionals. The selection of healthcare system access affects the time of hospital arrival. The active participation of the primary team affects the activation processes of Rapid Response Teams. The RRT position need to complement, rather than replace, an active and attentive primary care team. Rapid response systems (RRS) are established to enhance the safety of hospitalized patients experiencing rapid deterioration by promptly identifying early signs of decline, mobilizing a team of responders equipped to deliver critical care resources and interventions at the patient's location, facilitating swift intervention by the response team, and continuously assessing the system's efficacy and hospital-wide care processes. This approach aims to prevent deterioration that could result in life-threatening events, ensure timely therapy and resuscitation as necessary, and facilitate transfer to a higher level of care while fostering education and a culture of patient safety.